Impact of land use on woody aboveground biomass in Miombo woodlands of western Zambia – comparison of three allometric equations. Issue 3 (3rd July 2019) - Sichone, Priscilla; Schmiedel, Ute; Oldeland, Jens; Jürgens, Norbert
Abstract : Globally, the intensification of land use for agriculture, timber and fuel is considered the leading threat to the diversity and biomass of forests and woodlands. To suggest management options, it is important to understand the patterns and drivers of diversity, structure, biomass and carbon stock of woodland vegetation. In this study we used data from three sites in the Miombo woodlands of western Zambia, which are subject to low, medium and high land-use intensity. We sampled 20 plots of 1 000 m² at each of these sites. Woody vegetation was sampled for richness and structure to provide an understanding of the impact of land-use intensity. Woody plant species richness was not affected by land-use intensity. However, an ANOVA revealed that stem diameter at breast height (DBH) was higher at the low land-use intensity (national park) than at medium and high land-use intensities (selective timber harvest, and non-selective harvest for crop fields and timber). We tested three different allometric equations (one global and two regionally adapted) to determine woody aboveground biomass (AGB) and carbon stock at the three sites. The estimated AGB using the regionally adapted allometric equation of Ryan et al. and the global tropical equation of Brown et al. revealed that the AGB for low and high land-use intensity sites were significantly different from each other with the medium land-use intensity site being intermediate. We concluded that DBH and AGB estimations were influenced by the land-use intensity in the Miombo woodlands as suggested by other studies in the tropical forest and woodlands.